Impact of vedolizumab therapy on extra‐intestinal manifestations in patients with inflammatory bowel disease: a multicentre cohort study nested in the OBSERV‐IBD cohort. Issue 4 (18th December 2017) - Tadbiri, S.; Peyrin‐Biroulet, L.; Serrero, M.; Filippi, J.; Pariente, B.; Roblin, X.; Buisson, A.; Stefanescu, C.; Trang‐Poisson, C.; Altwegg, R.; Marteau, P.; Vaysse, T.; et al.
Summary: Background: The effectiveness of vedolizumab as a treatment for extraintestinal manifestations (EIM) is questionable due to its gut‐specificity. Aim: To assess effectiveness of vedolizumab for EIM in patients with inflammatory bowel disease (IBD) in a large real‐life experience cohort. Methods: Between June and December 2014, 173 patients with Crohn's disease and 121 with ulcerative colitis were treated with vedolizumab. Patients were followed until week 54. EIM activity was assessed at weeks 0, 6, 14, 22, 30 and 54 by using a 3‐step scale: complete remission, partial response and no response. Results: At baseline, 49 (16.7%) patients had EIMs of which 47 had inflammatory arthralgia/arthritis, four had cutaneous lesions and two had both rheumatologic and skin EIM. At week 54, 21 (44.7%) patients had complete remission for inflammatory arthralgia/arthritis and three (75%) for cutaneous EIM. In multivariate analysis, complete remission of inflammatory arthralgia/arthritis was associated with clinical remission of IBD (OR = 1.89, IC95% [1.05‐3.41], P = .03) and recent onset of inflammatory arthralgia/arthritis (OR = 1.99, IC95% [1.12‐3.52], P = .02). During the follow‐up period, 34 (13.8%) patients without any EIM at baseline, developed incident cases of inflammatory arthralgia/arthritis consisting mostly of peripheral arthralgia without evidence of arthritis and 14 (4.8%) incident cases of paradoxical skin manifestation. Conclusion: Vedolizumab therapy is commonly associated with improvement in EIM. This was associated with quiescent IBD and recent EIM. However, paradoxical skin manifestation and inflammatory arthralgia/arthritis may occur upon vedolizumab therapy. Abstract : Linked Content This article is linked to Barclay and Stamp paper. To view this article visithttps://doi.org/10.1111/apt.14465 .